Hydrides of YPd3: Electronic structure and dynamic stability. (12th January 2015) - Sharma, Ramesh; Dwivedi, Shalini; Sharma, Yamini
Abstract Ternary intermetallic YPd3 is known to exhibit superior hydrogen storage capacity compared to pure palladium. To understand the characteristics of YPd3 on hydrogenation, the ground state electronic and dynamical properties were computed by two computational methods, the full potential linearized plane wave and projector augmented wave methods within the density functional theory. Hydrogen can be inserted in YPd3 at various octahedral sites, giving rise to model structures YPd3H and YPd3H4 which retain the L12 crystal structure. The calculated energy bands confirm the metallic nature of YPd3 and also exhibit greater dispersion of bands with increase in hydrogen content. Large variations in the optical constants such as transmittance is observed (by ∼40% in the violet region) with insertion of hydrogen, YPd3 may have thus have applications as a sensing device for monitoring hydrogen for using hydrogen safely. The electronic component γ obtained from the temperature dependent specific heats, is related to the density of states at the Fermi level which may be co-related to instability of hydrides. The modes at Γ-point in YPd3H and at X and M-points in YPd3H4 give rise to high peaks in the imaginary frequency regime which could drive the dynamical instabilities. From the formation energies and phonon modes it is found that the monohydride YPd3H is more stable, thus occupation of the octahedral sites at 2Y4Pd by hydrogen atoms results in greater dynamic instability in YPd3.